IMPACT OF SHORT-TERM IV PARACETAMOL IN HIGH RISK NEONATES. Issue 8 (11th July 2014) - Windscheif, P; Mishra, G; Welsh, R; Lakhoo, K
Abstract : Aim: The aim of this study is to prospectively assess the impact of short term intravenous (IV) paracetamol on the liver function of high risk neonates. Methods: All neonates who received regular IV paracetamol for at least two days dosed 7.5 mg/kg 6-hourly were included in the study. The study was also confined to post-operative neonates who were receiving parenteral nutrition (TPN), morphine and antibiotics. Data was taken from a database system registered as a service evaluation tool with the local hospital. Data on twenty three neonates (from November 2009 to July 2013) was recorded out of which 7 have been managed for pain post-operatively with gastroschisis, 5 with necrotising enterocolitis (NEC), 3 tracheoesophageal fistula, 2 abdominal pathology, 2 duodenal atresia 1 exomphalus, 1 oesophagectomy, 1 thoractomy, and 1 intestinal ileal perforation. All neonates had treatment with IV paracetamol at the above dose for a median of 6 days (range 2–16 days). The treatment started at median postnatal age of 14 days (0 to 90 days). The median post-conceptual age was 33 weeks (25 to 40 weeks) and median birth weight was 1.6 kg (0.5 to 3.1 kg). All the babies have been on TPN (10 intralipid®, 13 SMOF ® ), antibiotics and morphine for whole period (except for 2 neonates who stopped morphine 1day earlier, for 1 who stopped 2 days earlier, and for 1 with the longest treatment of 16 days stopped morphine 6 days earlier). Results from routine blood samples for alanine transferase (ALT) and albumin were documented from the day of paracetamol initiation, at one to two days, and five to seven days after the final dose of IV paracetamol. Results: Sixteen (69%) neonates did not show any liver-impairment, 2 (8.7%) have had liver-impairment at initiation but this resolved during the course, 3 (13%) had a mild liver impairment on day 5 to 7 after stopping regular IV paracetamol which resolved, 2 (8.7%) had acute liver impairment mainly due to severe sepsis. ALT mean was at day of IV paracetamol initiation 20 U/L (range <8 to 73 U/L), at one to two days 27U/L (<8 to 214 U/L), and five to seven days 40 U/L (<8 to 369 U/L) after the final dose of paracetamol. Albumin mean was at day of initiation 27 g/L (range 20 to 36 g/L), at one to two days 26 (17 to 34 g/L), and five to seven days 29 g/L (17 to 41 g/L) after the final dose of IV paracetamol. The liver function improved further with resolving sepsis. Conclusion: Short duration of IV paracetamol treatment in post-operative neonates on TPN, morphine and antibiotics has minimal impact on liver function in the absence of severe sepsis.